Strengthening social ties in vulnerable cities - Jean-Christophe Levassor (Field Actions Science Reports, 2018)
Le Pile in east Roubaix has been particularly hard-hit by the industrial and financial crisis. Over 40% of the neighborhood’s residents live under the poverty line (€642 a month for a person living alone). Social divisions are clear to see and recreating spaces where people can interact and make contact with each other is a key challenge in building resilience for the future. These social divisions will become worse without a proactive policy to combat them, and may be further exacerbated by the digital revolution. If nothing is done to restore harmonious co-existence in the community, positive initiatives such as urban farming and zero waste will never have an effect beyond a limited circle of insiders.Located in this deprived neighborhood, La Condition Publique is a creative laboratory at the crossroad between art, culture and the imperatives of urban renewal and sustainability. Its aim is to recreate ties and spaces between different actors across the territory – residents, nonprofits, businesses, etc. – to support urban renovation and foster resilience.